Development of tin (IV) oxide based catalyst for carbon monoxide emission control - Imran Syakir, Mohamad (Penerbit Universiti Teknikal Malaysia Melaka, 2009)

(untitled)
Tin (IV) oxide has been recognized as an alternative catalyst for carbon monoxide gas treatment generated from vehicular and industrial activities. Carbon monoxide is a poisonous gas produce from incomplete burning of hydrocarbon based fuel and emitted directly from vehicles tailpipes which can affect human health. In this research, tin (IV) oxide was used as a catalyst with the addition of cobalt (II) oxide and nickel (II) oxide as dopants, prepared by modification of sol-gel method. The catalytic ability was tested towards the oxidation of carbon monoxide using Continuous Fixed Bed Reactor (SELOX) instrument. Two catalysts, ECAT1-400 calcined at 400°C and ECAT2-600 calcined at 600°C gave a promising catalytic ability towards carbon monoxide oxidation. Both catalysts completed the carbon monoxide oxidation to carbon dioxide at 215°C and 200°C (commercial catalyst, Pt/Al2O3 at 200°C). Several techniques were used in this research to characterize the physical and chemical properties of the catalyst materials. The nitrogen adsorption analysis reveals that the best prepared catalyst, ECAT2-600 is in form of mesopore, open cylindrical in shaped with pore diameter of 10nm. The x-ray diffraction analysis shows the presence of SnO2 tetragonal and Co3O4 cubic phase which act as the active site in the catalytic oxidation. The existence of cobalt oxide (in a mixture of Co2+ and Co3+) expected to contribute the excellent oxidation of carbon monoxide.